Implementasi Kurikulum Merdeka Belajar-Kampus Merdeka (MBKM) dalam menanamkan Nilai-Nilai Pendidikan Islam Multikultural di Universitas Yudharta Pasuruan - Zakkiyah, Kuny; Marzuki, Ahmad; Yusuf, Achmad (CV. Satria Jaya, 2023)
Yudharta Pasuruan University is a tertiary institution that has implemented the MBKM curriculum by instilling the values ​​of multicultural Islamic education aimed at educating and creating a generation that respects differences in ethnicity, religion, race, ethnicity, and culture in Indonesia which are diverse and multicultural. The purpose of this study was to analyze the implementation of the MBKM curriculum at Yudharta University, Pasuruan, and to instill the values ​​of Multicultural Islamic Education through the MBKM curriculum at Yudharta University, Pasuruan. The approach used is a qualitative approach supported by descriptive data. As for data collection techniques using active participation observation techniques, interviews, and documentation studies. The data analysis technique uses the interactive analysis model of Miles, Huberman and Saldana, namely data condensation, data presentation, and drawing conclusions. The results of this study indicate that: 1) Implementation of the MBKM curriculum at Yudharta University Pasuruan in 2020 to improve the quality of higher education and the relevance of tertiary institutions according to the needs of society and industry by involving several aspects, such as curriculum flexibility, fulfillment of students' learning rights to gain learning experience in outside the study program, the involvement of students and lecturers, especially FAI Islamic Religious Education (PAI) study programs in teaching campus programs, collaboration with the world of work, improving the quality of teaching, research and innovation. 2) Instilling the Values ​​of Multicultural Islamic Education through the MBKM curriculum at Yudharta University Pasuruan includes; (a) at-Ta’aruf, (b) at-Tawassuth, (c) at-Tasamuh, (d) at-Ta’awun, dan (e) at-Tawazun.